Collision induced two-pulsed photon echo at the transition 0–1 in a weak longitudinal magnetic field. (29th October 2015) - Rubtsova, N N; Gol'dort, V G; Ishchenko, V N; Khvorostov, E B; Kochubei, S A; Reshetov, V A
Abstract: It was shown experimentally in ytterbium vapour at the transition (6s 2 ) 1 S0 (6s6p) 3 P1 (type ), that the weak longitudinal magnetic field destroys the collision induced two-pulsed photon echo generated in a gas mixture with heavy atomic buffer; in agreement with theoretical prediction.